Design, application and verification of a novel system utilizing bacteria and microalgae to treat swine farm wastewater and produce value-added biomass - Zhen, Xin; Li, Yali; Qiang, Jingwen; Tang, Manyu; Hua, Wei; Wang, Wanqing; Wu, Shuang; Perkins, Phil; Ruan, Roger; Cheng, Yanling (International Journal of Agricultural and Biological Engineering, 2023)
Swine farm wastewater is extremely harmful to the environment if not treated before it is discharged. In this study, a system was developed and optimized for testing the high levels of organic matter in swine farm wastewater utilizing a microalgae/bacteria co-culture combined with a novel closed-loop extraction and dilution process. Importantly, the system produces biomass that also could be harvested and used in value-added applications. The efficacy of biomass as a biofertilizer was demonstrated by using a model plant of Arabidopsis. In addition, the analysis of biomass indicates that it also has potential as a source for biofuel. After a 20-d cultivation period, a yield of biomass was achieved to 2.063 g /L of wastewater. The highest removal rates recorded in steady state conditions were: 13.8 mg/L•d of Total Nitrogen (TN); 11.5 mg/L•d of Ammonia Nitrogen (NH4+-N); 24.8 mg/L•d of Chemical Oxygen Demand (COD); and 16.9 mg/L•d of Total Phosphorus (TP). After cultivation, the composition of the biomass was analyzed on a dry basis; the major components were protein (44.9%), lipids (24.6%), carbohydrates (19.9%), Chlorophyll-A (2.75%), Chlorophyll-B (1.66%), and carotenoids (0.57%). This biomass was diluted with water (5% by weight) and used as a biofertilizer to grow Arabidopsis. The results showed that the average root and stem lengths of Arabidopsis were 43.0% and 55.0% longer compared to those of the control group. Additionally, the number of leaves and the maximum leaf length increased by 30.2% and 39.7%; and the fresh and dry leaf weights increased by 44.0% and 33.7%, respectively. These results demonstrate the efficacy of this system for treating swine farm wastewater whilst simultaneously producing a value-added microalgae/bacteria biomass. This paper also demonstrated the use of biomass as a fertilizer for cultivating a value-added crop and, based on the compositional analyses, propose that the biomass could be used as a raw material for biofuel production due to its high lipid content of 24.6%. By constructing a microalgae/bacteria symbiosis system, Swine farm wastewater can be treated as resources utilizing producing value-added biomass with demonstrated efficacy as a biofertilizer.Key words: bacteria-microalgae, swine wastewater, environmental impact, value-added biomass, biofertilizerDOI: 10.25165/j.ijabe.20231604.8250Citation: Zhen X, Li Y L, Qiang J W, Tang M Y, Hua W, Wang W Q, et al. Design, application and verification of a novel system utilizing bacteria and microalgae to treat swine farm wastewater and produce value-added biomass. Int J Agric & Biol Eng, 2023; 16(4): 222-230.